1987
DOI: 10.1037/0278-6133.6.6.495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of symptoms and aging attribution on emotions and coping.

Abstract: Two experimental studies and a large field study were designed to examine how symptom severity, symptom duration, symptom ambiguity, and the association of symptoms with aging affected emotional responses and coping with illness threats. In Study 1, 280 respondents from the surrounding community reported the emotional and coping responses they would manifest to scenarios that varied the severity, duration, and ambiguity (i.e., labeled vs. unlabeled) of a common set of symptoms. Severity had more of an impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 25 publications
8
86
0
Order By: Relevance
“…24 Vitaliano et al (1985) Ways of Coping Checklist (modified) Self-report measure Lazarus (1981), Moos (1976Moos ( , 1977. Focus from Antonovsky (1979), Lazarus (1981), and Prohaska et al (1987) Self-report measure Coping with illness…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Vitaliano et al (1985) Ways of Coping Checklist (modified) Self-report measure Lazarus (1981), Moos (1976Moos ( , 1977. Focus from Antonovsky (1979), Lazarus (1981), and Prohaska et al (1987) Self-report measure Coping with illness…”
Section: Resultsmentioning
confidence: 99%
“…25 Andersson & Ekdahl (1992) Appraisal and Coping Questionnaire Coping with chronic disease 43 Austin et al (1991) Coping Health Inventory for Children 73 Altshuler et al (1995) 2 Amirkhan (1990) Coping Strategy Indicator 26 Bowman (1990) Marital Coping Inventory 44 Ayers et al (1996) Children's Coping Strategies Checklist How I Coped Under Pressure Scale 74 Altshuler & Ruble (1989) 3 Aspinwall & Taylor (1992) Ways of Coping Checklist 27 Burt & Katz (1988) How I Deal With Things Coping with rape 45 Brodzinsky et al (1992) Coping Scale for Children and Youth 75 Ayers et al (1989), cited in Kliewer (1991) 53 Gil et al (1991) Coping Strategies Questionnaire for Sickle Cell Disease 83 Dickey & Henderson (1989) 12 Hobfoll et al (1994) Preliminary Strategic Approach to Coping Scale 36 Marriage, parenting, household economics, and occupation 54 Glyshaw et al (1989) 84 Hardy et al (1993) 13 Holohan & Moos (1987) 37 Prohaska et al (1987) Coping with illness 55 Halstead et al (1993 Adapted from Lazarus & Folkman (1984) and Greene & Yando (1980 Three higher order factors derived from problem-focused vs. emotion-focused and active vs. passive theoretical distinctions. Lower order strategies from review of general and painspecific coping literature.…”
mentioning
confidence: 99%
“…Other researchers have shown that some caregivers tend to attribute dementia to 'change of personality due to old age, which they cannot do anything about' (Boise et al, 1999;Bond et al, 2005). Prohaska et al (1987) noted that people generally tend to attribute symptoms of dementia to aging, especially older individuals or those with mild dementia.…”
Section: Discussionmentioning
confidence: 97%
“…Prohaska et al (1987) noted that people generally tend to attribute their symptoms to aging, especially older individuals or those with less-severe symptoms. Hence, the psychosocial effects of a disease might vary between patients depending upon the point in their lives at which the symptoms occur.…”
Section: Discussionmentioning
confidence: 97%